HIV risk associated with serum medroxyprogesterone acetate levels among women in East and southern Africa. (15th March 2019) - Heffron, Renee; Stalter, Randy; Pyra, Maria; Nanda, Kavita; Erikson, David W.; Hladik, Florian; Blue, Steven W.; Davis, Nicole L.; Mugo, Nelly; Kourtis, Athena P.; Lingappa, Jairam R.; Baeten, Jared M.
Abstract : Background: Some observational studies have found increased HIV risk associated with self-reported use of injectable depot medroxyprogesterone acetate. Testing blood samples for medroxyprogesterone acetate (MPA), the progestin in depot medroxyprogesterone acetate, permits validation of self-reported data, and exploration of whether potential HIV risk is correlated with MPA levels, which are highest soon after injection. Methods: We conducted a case–control study testing archived serum from women who participated in three longitudinal studies of HIV prevention in East and southern Africa. Case samples, from women who acquired HIV, were from visits that occurred at or immediately prior to the first evidence of HIV infection. Secondary analyses restricted to case samples collected within 15 and 30 days of the estimated date of HIV infection. Matched control samples were from women who remained HIV uninfected. We used multivariable conditional logistic regression to compare exogenous hormone levels, quantified through mass spectrometry, among cases and controls. Results: When restricted to cases with samples collected within 15 days or less of estimated date of HIV infection, MPA detection was more frequent among women who acquired HIV (adjusted odds ratio = 2.75, 95% confidence interval 1.22–6.19). In this subset, the increase in HIV risk was only among samples with MPA detected at a low level of 0.02–0.50 ng/ml: 36.7% of cases and 9.4% of controls, adjusted odds ratio = 6.03, 95% confidence interval 2.50–14.54. Conclusion: Detection of MPA at low levels close to the estimated time of HIV acquisition was significantly more frequent among women who acquired HIV. Studies are needed that explore biological mechanisms elicited by any MPA level and HIV risk.